EVALUASI KEBIJAKAN PRESIDEN TENTANG BENCANA LUMPUR PANAS TERHADAP PEREKONOMIAN DI KABUPATEN SIDOARJO - Yuniarto, Alvian Bagus (Jurnal Administrasi Publik, 2016)
Accountability Policy Evaluation PT. Lapindo Brantas Against Economic Community in Sidoarjo. Hot mud disaster has made economic to decline because of the disaster people have drowned their residence, especially jobs and their livelihood as well as educational facilities and places of worship. With the existence of the incident public life struggling to feed themselves and their families for the sake of economic progress in the future.